ASAM LEMAK TRANS DALAM MAKANAN DAN PENGARUHNYA TERHADAP KESEHATAN [Trans Fatty Acids in Foods and Their Effects on Human Health] - Jansen Silalahi; Sanggam Dera Rosa Tampubolon (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2002)
Unsaturated fatty acids are present in natural dietary fat as cis-isomer and, only small amount is in the form of trans-isomer fatty acids (TFA) especially in food of ruminant- animal origin. Trans fatty acids are generated in fat during hydrogenation process and by heating treatment at 180 oC or above. Negative effects of TFA are of increasing concern as they are found to have more risk than saturated fatty acids with regard to coronary heard disease incidences. When consumed in large amounts (more than 2 % of total energy) TFA increases total cholesterol levels by increasing low density lipoprotein (LDL) and decreasing high density lipoprotein (HDL). Therefore the resulting effects may be twice as much as that caused by saturated fatty acids because saturated fatty acids increase LDL without affecting HDL. This article reviews trans fatty acids in foods and their effects on human health.